Disruptive innovation, the episteme and technology-enhanced learning in higher education. (1st June 2021) - Flavin, Michael
Abstract : This paper combines the theory of disruptive innovation with Foucault's concept of the episteme, in order to analyse the extent to which the integration of Foucauldian analysis clarifies understandings of disruptive innovation; the process by which innovation happens; and its applications in higher education. The theory of disruptive innovation is summarized, as is the episteme, and the idea of skeuomorphic design is used to link disruptive innovation and the episteme, showing how innovation can happen. Disruptive innovation, the episteme and skeuomorphic design are applied to three, specific technologies – Second Life, the massive open online course and the virtual learning environment – arguing that all three offer little or no innovation. The paper contributes to studies on innovation in technology-enhanced learning by applying a novel theoretical framework with the potential for new and predictive insights. The paper links disruptive innovation with Foucault's concept of the episteme and with skeuomorphic design to argue for the emergence of a new, neoliberal episteme in which technology itself is central.